STRUKTUR MODAL, MODAL INTELEKTUAL, DAN NILAI PERUSAHAAN PADA PERBANKAN INDONESIA - Lia Uzliawati; Rita Rosiana; Desi Kurniasari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
This study aimed to analyze the effect of capital structure and intellectual capital on firm value. Capital structure in this study measured by Long Term Debt to Equity Ratio (LTDER). The model that used to measure intellectual capital was Pulic model (1998) Value Added Intellectual Coefficient (VAIC). The ratio that used to measure firm value was Price to Book Value Ratio (PBV). This study used conventional banking companies listed in Indonesia Stock Exchange during the period 2008-2013 with a total of 192 sample used were firm observation years. The analysis model used in this study is multiple linier regression using SPSS software version 19.0. Based on the results of multiple linier regression, the study found that the capital structure has no effect on firm value and intellectual capital has a positives effect on firm value. Keywords: Capital Structure, Intellectual Capital, Firm Value, PBV, dan Perbankan